2011
DOI: 10.1074/jbc.m111.225805
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Restriction Mimetic 2-Deoxyglucose Antagonizes Doxorubicin-induced Cardiomyocyte Death by Multiple Mechanisms

Abstract: Caloric restriction (CR) is a dietary intervention known to enhance cardiovascular health. The glucose analog 2-deoxy-Dglucose (2-DG) mimics CR effects in several animal models. However, whether 2-DG is beneficial to the heart remains obscure. Here, we tested the ability of 2-DG to reduce cardiomyocyte death triggered by doxorubicin (DOX, 1 M), an antitumor drug that can cause heart failure. Treatment of neonatal rat cardiomyocytes with 0.5 mM 2-DG dramatically suppressed DOX cytotoxicity as indicated by a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 84 publications
4
57
0
Order By: Relevance
“…NRCs were pretreated with resveratrol (10 M) for 12 h and then Resveratrol Inhibits Doxorubicin Cardiotoxicity exposed to DOX (1 M) for another 18 h. The lysosomal inhibitor BFA (50 nM) was added 6 h before the cells were examined for GFP-LC3 dots (AVs) under a confocal microscope. In line with previous reports Kobayashi et al, 2010;Chen et al, 2011), DOX triggered the formation of numerous AVs as indicated by the GFP-LC3 dots, which was further increased by BFA treatment ( Fig. 2A), suggesting that DOX accelerated autophagic flux in cardiomyocytes.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…NRCs were pretreated with resveratrol (10 M) for 12 h and then Resveratrol Inhibits Doxorubicin Cardiotoxicity exposed to DOX (1 M) for another 18 h. The lysosomal inhibitor BFA (50 nM) was added 6 h before the cells were examined for GFP-LC3 dots (AVs) under a confocal microscope. In line with previous reports Kobayashi et al, 2010;Chen et al, 2011), DOX triggered the formation of numerous AVs as indicated by the GFP-LC3 dots, which was further increased by BFA treatment ( Fig. 2A), suggesting that DOX accelerated autophagic flux in cardiomyocytes.…”
Section: Resultssupporting
confidence: 78%
“…DOX can induce autophagy in cardiomyocytes, which is a major mechanism of DOX cardiotoxicity Kobayashi et al, 2010;Chen et al, 2011). Therefore, we tested whether resveratrol could inhibit DOXinduced autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the role of autophagy in Dox-induced cardiotoxicity, whether protective or pathological, is still under question. Therefore, the underlying mechanism(s) of fasting-induced cardioprotection against Dox remains to be determined and is likely due to a combination of mechanisms [30] .…”
Section: Mechanism Of Fasting-induced Cardioprotection Against Dox Tomentioning
confidence: 99%
“…Microscopy revealed attenuation of LV dilatation, myocardial atrophy, and fibrosis [29] . In vitro, a caloric restriction mimetic, 2-deoxyglucose (2-DG), was shown to exhibit cardioprotective properties against Dox using neonatal rat cardiomyocytes isolated from 0-2 d old Harlan Sprague-Dawley rat neonates [30] . Thus, the literature supports that fasting may be an effective regimen to protect against Dox-induced cardiotoxicity.…”
Section: Dox-induced Cardiotoxicitymentioning
confidence: 99%